The social profile of the amputee patient in rehabilitation - Lima, Laís Batista de; Correia, Viviane Duarte; Salimene, Arlete Camargo de Melo (Acta Fisiátrica, 2016)
Considerations about amputee patients need to go beyond their physical rehabilitation. As an integral process, rehabilitation includes the presence of a social worker, which is indispensable during the treatment; this is a professional that provides a way to gradually provide social inclusion considering their new situation. Objective: This study made a social profile of the amputee inpatients who were treated in the Institute of Physical Medicine and Rehabilitation/IMREA, in the city of São Paulo/SP. Methods: This was a retrospective study: quantitative regarding the collection of data, and qualitative as an analysis of the basis of the dialectical materialist perspective. For the development of this study, a sampling of medical records between November 2014 and July 2015 was surveyed. Results: Information was collected coming from Social Assessment institutional protocol, a professional operating and technical tool, such as age; sex; marital status; per capita income; region of origin; level of education; social security benefits, and whether they had access to rehabilitation treatment elsewhere. Conclusion: This work highlights the importance of professional social work as part of the interdisciplinary team in the process of rehabilitation of the amputee, thus enabling one to know the individual in his entirety.